2008
DOI: 10.1111/j.1750-3841.2008.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Precursors and Methylpyrazines in Underfermented Cocoa Beans Induced by Endogenous Carboxypeptidase

Abstract: Cocoa-specific aroma precursors and methylpyrazines in underfermented cocoa beans obtained from fermentation induced by indigenous carboxypeptidase have been investigated. Fermentation conditions and cocoa bean components were analyzed during 0 to 3 d of fermentation. Underfermented cocoa beans were characterized as having hydrophilic peptides and free hydrophobic amino acids much higher than unfermented ones. These 2 key components of cocoa aroma precursors may be produced from the breakdown of proteins and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…Furthermore, the hydrophobic amino acids are considered as the most potent precursor formation for methylpirazins. The study of Jinap et al (2008 and2010) and Yusep et al (2002) showed that hydrophobic free amino acids and acid group amino acids directly contribute to the formation of cocoa flavor because they act as substrates for Maillard reaction to form methylpirazins. Methylpirazin is allegedly associated with chocolate flavor intensity, while the hydrophobic amino acids are considered to be the most potent precursor formation for methylpirazins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the hydrophobic amino acids are considered as the most potent precursor formation for methylpirazins. The study of Jinap et al (2008 and2010) and Yusep et al (2002) showed that hydrophobic free amino acids and acid group amino acids directly contribute to the formation of cocoa flavor because they act as substrates for Maillard reaction to form methylpirazins. Methylpirazin is allegedly associated with chocolate flavor intensity, while the hydrophobic amino acids are considered to be the most potent precursor formation for methylpirazins.…”
Section: Resultsmentioning
confidence: 99%
“…Those are significantly different with amino acids produced by cacao beans of fermented 72, 96 and 120 h. Amino acid deteriment specifically alannine 1.37 ± 0.01 increase to 1.65 ± 0.01, tyrosine 0.78±0.01 decrease to 0.63±0.01, valine 0.82±0.01 increase to 0.95 ± 0.01, phenylalanine 1.26±0.01 decrease to 1.19±0.01, isoleucine 0.92±0.01 just same after 120 h and leucine 1.41±0.01 increase to 1.48±0.01.Most types of amino acids in the cacao beans are aspartic, glutamic and lysine. Yusep et al (2002) and Jinap et al (2008) described that amino acid is a precursor of certain aroma that acts as a substrate for a Maillard reaction to form methylpyrazines (Eichner et al, 1994).…”
Section: Materials and Methods Preparation Of Cocoa Beansmentioning
confidence: 99%
“…Furthermore, the hydrophobic amino acids are considered as the most potent precursor formation for methylpirazins. The study of Jinap et al (2008Jinap et al ( , 2010 and Yusep et al (2002) showed that hydrophobic free amino acids and acid group amino acids directly contribute to the formation of cocoa flavor because they act as substrates for Maillard reaction to form methylpirazins. Methylpirazin is allegedly associated with chocolate flavor intensity, while the hydrophobic amino acids are considered to be the most potent precursor formation for methylpirazins.…”
Section: Discussionmentioning
confidence: 99%
“…Most types of amino acids in the cacao beans Sulawesi clone are aspartic, glutamic and lysine. Yusep et al (2002) and Jinap et al (2008) described that amino acid is a precursor of certain aroma that acts as a substrate for a Maillard reaction to form methylpyrazines (Eichner et al, 1994).…”
Section: Amino Acid Of Sulawesi Clonementioning
confidence: 99%
“…Pengukuran nilai pH biji kakao berdasarkan metode Jinap, Ikrawan, Bakar, Saari, & Lioe (2008). Biji kakao sebanyak 5 g yang telah dihaluskan dengan mortar dimasukkan ke dalam erlenmeyer 150 ml, kemudian ditambahkan 45 ml akuades dan diaduk menggunakan pengaduk magnetik selama 10 menit.…”
Section: Pengukuran Nilai Ph Biji Kakaounclassified